The dynamics of Tahfiz institutions: A case study of three best practice models of Tahfiz education in Malaysia - Hazlina Abdullah; Saad N.S.M.; Tibek S.R.; Ghani Z.A.; Amir Husin Mohd Nor; Ishak M.; Sulaiman A.; Ismail N.A.; Darmi R.; Idrus M.M.; Jaafar N.N.; Gunardi S. (Sakarya University, 2024)
Indexed by SCOPUS